Analisis keterampilan bercerita pada materi cerita rakyat bahasa jawa kelas iv sekolah dasar - Destya Nuryandara Fadillah; Retno Winarni; Joko Daryanto (Universitas Sebelas Maret, 2022)
This study aims to: 1) describe the analysis of the storytelling skills of students; 2) mention the obstacles experienced by students in storytelling skills; and 3) describe solutions to overcome the obstacles experienced in storytelling skills. This study uses a qualitative descriptive research method. The subjects of this study were fourth grade students of SD Negeri Sukorejo Klaten. Research data were collected through data collection techniques of observation, interviews and document studies. The data analysis technique uses the Miles and Huberman model. The results showed that the fourth grade students of SD Negeri Sukorejo Klaten in analyzing storytelling skills on Javanese folklore material were still less successful in the aspects of voice volume, expression suitability, story sequence logic suitability, and fluency. Constraints experienced by students in storytelling activities are not confident, not brave, afraid of making mistakes, nervous, embarrassed, unable to express expressions, and making class noise. The solution is to do active and fun learning as well as habituation to students to be confident and dare to appear so that the obstacles experienced during storytelling can be overcome.